Performance analysis of a novel bifacial solar photothermic and radiative cooling module. (15th May 2021) - Hu, Mingke; Zhao, Bin; Ao, Xianze; Suhendri,; Cao, Jingyu; Wang, Qiliang; Riffat, Saffa; Su, Yuehong; Pei, Gang
Graphical abstract: Highlights: A bifacial solar photothermic and radiative cooling (PT-RC) module was proposed. The module can flexibly switch between solar heating and radiative cooling modes. The module shows 83.3% thermal efficiency with solar irradiance of 1000 W/m 2 . The module reaches up to 69.9 W/m 2 net radiative cooling power. Its total energy gain throughout a day is 5.36 times that of a radiative cooler. Abstract: Solar energy and universe coldness are two renewable and clean energy constantly sent from outer space to the earth. Solar thermal collectors and radiative coolers respectively harvest heat and cooling energy in this context. However, their static and monofunctional spectral properties mismatch energy demands in regions with large air temperature fluctuations throughout the whole year. In this work, a rotatable bifacial solar photothermic and radiative cooling (PT-RC) module capable of flexibly switch between solar heating and radiative cooling modes is proposed to realize smart thermal management. In the solar heating mode with solar irradiance of 1000 W/m 2, the PT-RC module shows 83.3% solar thermal efficiency, which is even slightly higher than that of a typical solar thermal module. In the radiative cooling mode, the PT-RC module reaches up to 69.9 W/m 2 net radiative cooling power and 11.7 °C temperature reduction. The heat and cooling energy of the PT-RC module throughout a typical day in Hefei city totals 17.7 MJ. This bifacial PT-RC module provides an alternative solution for integrating solar energy and universe coldness and shows potential in flexibly providing heat and cooling energy in different seasons.